A Comprehensive Study of Architects’ and Non-Architects’ Perceptions of Building Facades through the Lens of Environmental Perception Theory - Srijon, Nayem Ahasan; Islam, Mohammed Zakiul (MAJ - Malaysia Architectural Journal, 2025)
Human perception is a complex process influenced by numerous factors, including age, gender, education, religion, cultural background, and individual experiences. Understanding these perceptions in architecture and urban design is crucial for creating spaces that resonate with users. It is the most significant characteristic for conveying the appearance of the built environment. However, a disparity often exists among architects’ and non-architects' preferences, resulting in a communication gap and user dissatisfaction with design outcomes. Sometimes, clients must accept the undesirable opinions of the architect against their will. The research investigates the differential perceptions of building facades among architects and non-architects. Through a combination of questionnaire surveys, Likert scale assessments, and interviews, insights were gathered regarding the aesthetic preferences of both groups. The findings reveal that architects and non-architects prioritize geometric features in facade design and decorations. Architects favor minimalist decorations, viewing excessive ornamentation as detracting from aesthetics. Additionally, architects demonstrate heightened awareness of building materials, reflecting their direct involvement in the construction process, whereas non-architects exhibit a greater sensitivity to using glass in facades. Both groups share similar color perceptions, with windows being the least perceived feature. So, the research emphasizes the significance of effective communication and collaboration between architects and users. By acknowledging and integrating user preferences alongside architectural expertise, architects can develop built environments that are aesthetically pleasing and resonate with a broader audience.